The experiences of the caring dyad: (Un)articulated realities of living with cardiometabolic risk, metabolic syndrome and related diseases in severe mental illness - Dolly Sud; Ian Maidment; Eleanor Bradley; Jonathan Tritter (Wiley, 2021)
Abstract Background Informal carers play an important role in the care of patients with mental illness. Little is known of the relationship experience of the patient and their informal carer (caring dyad) as the context for the intersection between physical and mental health. Aim This study aimed to explore the impact of comorbid cardiometabolic risk (CMR), metabolic syndrome (MetS) and related diseases and severe mental illness (SMI) on the caring dyad. Design Between October 2018 and March 2020, we conducted 11 in‐depth semi‐structured interviews across 6 adult caring dyads, interviewing each individual separately. Setting Dyads were recruited within the United Kingdom; informal carers were nominated by the patient as a person who provided a significant amount of support. Variable Being Studied Participants were asked about the impacts of illness and caring on daily life. Data Analysis Data were analysed at the dyad level using thematic analysis, comparing and contrasting responses from each individual. Results Themes were identified: enhanced closeness, dissonance and balance within the caring dyad. Discussion and Conclusions This study uses a particular population of patients with comorbid CMR factors, MetS and related diseases and SMI and their informal carers to explore the relevance and utility of caring dyads as an analytical framework to inform practice and policy. Future interventions should consider factors impacting on dyadic relationships to formulate effective and sustainable dyadic care and treatment to improve health outcomes for both patients with SMI and their informal carers. Patient/Public Involvement In this study, patients and informal carers were participants. Topic guides were piloted with a patient and informal carer.